(untitled) (Global Journal of Science Frontier Research, 2016)
This paper presents a new enhancement approach for infrared images. The idea behind this technique is based on that modifies the local luminance mean of an image and controls the local contrast as a function of the local Luminance mean of the image. The algorithm first separates an image into LPF (low pass filtered) and HPF (high pass filtered) components. The LPF component then controls the amplitude of the HPF component to increase the local contrast. The LPF component is then subjected to a non linearity to modify the local luminance mean of the image and is combined with the processed HPF component. Finally, this approach is enhanced to get an infrared image with better visual details.